The perspective of staff members of two forensic psychiatric clinics in German-speaking Switzerland on the introduction of recovery orientation: An explorative study - Schoppmann, Susanne; Balensiefen, Joachim; Nienaber, André; Rogge, Stefan; Hachtel, Henning (Frontiers in Psychiatry, 2023)
Recovery orientation (RO) is directed on living a worthwhile life despite being impaired by the constraints of mental illness. Although being quite common in general psychiatry in Switzerland, the dual mission of forensic psychiatry – safeguarding and therapy – challenges the idea of establishing RO as a work philosophy in this context. This explorative study qualitatively investigates baseline expectations and professional perspectives of forensic staff members concerning the idea to establish RO in Swiss forensic psychiatric wards. Thereby, three central themes were worked out, namely ‘challenges associated with recovery’, ‘expected barriers’, and ‘possible recovery-oriented interventions’. From a general point of view, the staff members were uncertain whether RO-interventions can be introduced at all, and if so to what extent. This, on the one hand, had to do with structural obstacles such as security requirements; however, personal obstacles in the form of different, sometimes contradictory attitudes and ideals, and fearful anticipations – such as the loss of authority and power – also played a central role. As forensic-psychiatric wards are non-existent in Latin-speaking Switzerland, the study does only refer to the German-speaking language region.